2010
DOI: 10.1111/j.1464-5491.2009.02914.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐limb risk factors for falls in people with diabetes mellitus

Abstract: Simple clinical measures of gait velocity and ankle muscle strength may be used to identify people with DM at risk of falling, allowing preventative strategies to be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 31 publications
4
86
0
2
Order By: Relevance
“…Tinetti test, together with tests of muscle strength, tests for neuropathy and foot deformity, could point to the risk for falls in diabetic patients, so that preventive measures could be undertaken on time 10 . Patients suffering from diabetes type 2, whether they live in rural or urban settings, share similar risk factors for chronic falling, namely similar comorbidities and take similar kind and number of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Tinetti test, together with tests of muscle strength, tests for neuropathy and foot deformity, could point to the risk for falls in diabetic patients, so that preventive measures could be undertaken on time 10 . Patients suffering from diabetes type 2, whether they live in rural or urban settings, share similar risk factors for chronic falling, namely similar comorbidities and take similar kind and number of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This fact can be explained by increased double support values associated with decreased single support values, confirming the difficulty in maintaining the gait swing phase, which may indicate a balance deficit and hence, a greater risk of falling 18,19 . A previous study found a longer period of support in the gait of patients with DPN, suggesting that this was due to the generation of compensatory mechanisms of a musculoskeletal nature, as well as finding aggravations of other variables related to gait 4 .…”
Section: Discussionmentioning
confidence: 88%
“…poor cardiorespiratory functions, metabolic risk and poor quality of life) (Barbat-Artigas et al, 2010;Levinger et al, 2009;MacGilchrist et al, 2010). Abdominal muscle endurance is an essential component of fitness for health, maintaining proper alignment, prevents low back pain and supporting movements of both the lower and upper extremities in activities of daily living and work performance (Hildenbrand & Noble, 2004;McNeil et al, 1980).…”
Section: Disscusionmentioning
confidence: 99%
“…Low muscle strength has been shown to be associated with poor cardiorespiratory functions and an increased risk of falling (Barbat-Artigas et al, 2010;MacGilchrist et al, 2010). Levinger et al (2009) also described low muscle strength may also be associated with an unfavorable metabolic risk profile, which may affect exercise capacity, and the capacity to perform activities of daily living and quality of life.…”
Section: Introductionmentioning
confidence: 99%